Intensity of the phenomenon of refusal to subject children to preventive vaccinations in the years 2002-2016 based on analysis of primary health care medical records - Sochocka, Lucyna; Widera, Anna; Szwamel, Katarzyna (Medical Science Pulse, 2018)
Background. Vaccinations are the most effective method for preventing infectious diseases. Massive implementation of long-term vaccinations strategies has resulted in elimination or a reduced incidence of many infectious diseases. Aim of the study. To evaluate the intensity of the phenomenon of refusal to subject children to preventive vaccinations by attempting to characterize the parental group who refuse to vaccinate their children, determining the type and number of unrealized vaccinations, and identifying the reasons for being unvaccinated. Material and methods. The research material was medical records from the Non-Public Heath Care Unit in Opole. It concerned implementation of the Protective Vaccine Program over the years 2002-2016. A method of retrospective analysis of medical records using modern technology was applied. Results. The phenomenon of refusal to subject children to preventive vaccinations is increasing. In the years 2002-2016, our retrospective analysis identified that 81 vaccinations (0.8% of the 10,057 vaccinations) were not carried out. The largest percentage of unrealized vaccinations involved hepatitis B (23.4%). Parents refusing to vaccinate their children were adults (Median = 31 years old, range: 27-36 years) and predominantly living in cities (87.88%). The reasons for abandoning mandatory vaccinations were not reporting with a child for vaccination (48.1%), deliberate refusal to subject a child to the vaccination (28.4%) and postponement of vaccination due to contraindications (23.5%). Conclusions. The vaccination coverage level in the study area was assessed as satisfactory and is comparable to the results obtained on the national scale. The scale of the refusal for preventive vaccinations is not an epidemiological threat currently. However, it requires constant monitoring, and educational and information actions directed at parents/guardians.